Digitalization as "an Agent of Social Change" in a Supermarket Chain: Applying Blumer's Theory of Industrialization in Contemporary Society. Issue 4 (23rd July 2020) - Lehn, Dirk vom
Abstract : In this article I pursue Blumer's argument in Industrialization as an Agent of Social Change that social changes are the consequence of people's interpretation of technology. By examining oral history interviews with managers and other staff of the British supermarket chain Tesco I explore the relationship between "digitalization" and the organization of the business. The analysis reveals how the interviewees interpreted emerging computing technologies, and how the deployment of these technologies in the business impacted the material and ecological arrangement and the distribution of knowledge in the company. The article ends with a discussion of the relevance of Blumer's framework for contemporary studies of "digitalization" and social change.